2018
DOI: 10.1017/s1368980018003440
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Chinese famine exposure in early life on dietary patterns and chronic diseases of adults

Abstract: ObjectiveTo assess the effect of famine exposure during early life on dietary patterns, chronic diseases, and the interaction effect between famine exposure and dietary patterns on chronic diseases in adulthood.DesignCross-sectional study. Dietary patterns were derived by factor analysis. Multivariate quantile regression and log-binomial regression were used to evaluate the impact of famine exposure on dietary patterns, chronic diseases and the interaction effect between famine exposure and dietary patterns on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 42 publications
1
26
0
Order By: Relevance
“… 21 41 54 55 Three Chinese studies found increased risk of dyslipidaemia after childhood famine exposure between 0 and 12 years, with one also reporting an effect in the adolescent group (13–20 years). 50 56 57 A study of Leningrad Siege survivors found higher high-density lipoprotein (HDL) in exposed participants (p=0.008) but no difference in triglycerides compared with controls. 34 Only one Chinese study stratified analyses by sex and it found an increased risk of dyslipidaemia in women only.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 21 41 54 55 Three Chinese studies found increased risk of dyslipidaemia after childhood famine exposure between 0 and 12 years, with one also reporting an effect in the adolescent group (13–20 years). 50 56 57 A study of Leningrad Siege survivors found higher high-density lipoprotein (HDL) in exposed participants (p=0.008) but no difference in triglycerides compared with controls. 34 Only one Chinese study stratified analyses by sex and it found an increased risk of dyslipidaemia in women only.…”
Section: Resultsmentioning
confidence: 99%
“…Zhou et al50 China, adults45-60 years 0-2 years (n=160) 3-5 years (n=173) 6-8 years (n=141) NCDs ↑ T2D (0-2 years, 3-5 years) ↑ Hypercholesterolaemia (0-2 years) -/ -Dutch Hunger Winter (1944-1945) Idris et al 29 Netherlands, women~70 years 0-9 years (n=93) 10-18 years (n=54) Coronary artery calcifications, valve calcification ↑ Coronary calcium score (10-18 years) ↔ Valve calcification • / Portrait et al 31 Netherlands, adults 60-76 years 0-1 years (n=81) 1-5 years (n=293) 6-10 years (n=244) 11-14 years (n=181) Heart diseases, peripheral arterial diseases (PAD), T2D ↑ T2D, PAD (women, 11-14 years) • / • van Abeelen et al 27 Netherlands, women 49-70 years 0-9 years (n=n/r) 10-17 years (n=n/r) T2D ↑ T2D (0-9 years) • / • van Abeelen et al 28 Netherlands, women 49-70 years 0-9 years (n=2196) 10-17 years (n=1773) Coronary heart disease (CHD), stroke ↑ CHD (10-17 years) ↓ Stroke • / •Siege ofLeningrad (1941Leningrad ( -1944 …”
mentioning
confidence: 99%
“…Of these 71 articles, 24 were further excluded for various reasons (Appendix S1). Finally, 47 articles were included in the present meta‐analysis. The articles were published between 2006 and 2019, mostly published from 2014 onwards.…”
Section: Resultsmentioning
confidence: 99%
“…Foetal exposure to famine was associated with higher risks of T2DM (RR 1.37, 95% CI, 1.23‐1.52; Figure ), metabolic syndrome (RR 1.26, 95% CI, 1.07‐1.50; Figure ), hypertension (RR 1.30, 95% CI, 1.07‐1.57; Figure ), hyperglycaemia (RR 1.27, 95% CI, 1.11‐1.45; Figure ), dyslipidaemia (RR 1.48, 95% CI, 1.33‐1.66; Figure 2), obesity (RR 1.19, 95% CI, 1.02‐1.39; Figure ), overweight (RR 1.17, 95% CI, 1.07‐1.29; Figure ), coronary heart disease (RR 1.22, 95% CI, 1.00‐1.51; Figure ), and moderate‐to‐severe NAFLD (RR 1.66, 95% CI, 1.07‐2.57; Figure 3) . No association was observed for the risks of stroke (RR 1.21, 95% CI, 0.96‐1.52; Figure ) or mild NAFLD (RR 1.04, 95% CI, 0.64‐1.70; Figure 3) .…”
Section: Resultsmentioning
confidence: 99%
“…This could imply that the impact of famine on adulthood overweight/obesity could be exacerbated by lifestyle factors including smoking, unhealthy diets, and sedentary lifestyles [31]. The study of Zhou J et al, (2019) in Chinese study observed that the joint effect between famine and harmful dietary pattern could have serious consequences on later-life health outcomes [58].…”
Section: Height Amentioning
confidence: 99%